Mekanisme Pengangkutan Air pada Tanaman Allamanda chatartica - Nazilla Khoridatul Hidayah; Gatra Ervi Jayanti (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
Water transport in the plant body depends on the efficiency of xylem and phloem networks. This study aims to observe the role of transport tissues, especially xylem, in the process of water transportation in Allamanda cathartica plants. The research method was conducted with three different treatments on the plant stem: xylem and phloem open (control), xylem closed phloem open, and phloem closed xylem open. Each treatment was observed for 10 days to record the decrease in water level. Results showed that the treatment with open xylem absorbed the most water compared to the other treatments, while phloem closure had no significant impact on water absorption. This finding confirms that xylem is the main pathway in the transportation of water in plants, while phloem is more involved in the distribution of photosynthetic products.Keywords: Allamanda cathartica; phloem; transport tissue; xylem.